Damnation - McLean, Peter, 1972- (McLean, Peter, 1972- Burned Man novel., 2017)
"Don Drake is living rough in a sink estate on the outskirts of Edinburgh, doing cheap spells for even cheaper customers while fending off the local lowlifes. Six months ago, Don fled from London to Glasgow to track down his old girlfriend Debbie the alchemist. With the Burned Man gradually driving him mad, Don meets with an ancient and mysterious tramp-slash-magician, with disastrous consequences. Now his old accomplices must step in to save Don from himself, before he damns himself for good this time" -- provided by publisher.